Impact of Coronavirus Disease 2019 on Clinical Characteristics in Patients With Lung Cancer: A Large Single-Centre Retrospective Study - Zhang, Yu; Li, Jie; Li, Zhi-Ke; Yang, Xiyue; Bai, Jie; Liu, Lihua; Dai, Tangzhi; Feng, Gang; Li, Qiu; Du, Xiaobo (Frontiers in Oncology, 2021)
Lung cancer is the most common cancer malignancy worldwide. With the continuous spread of the coronavirus disease 2019 (COVID-19) globally, it is of great significance to explore the impact of this disease on the clinical characteristics of lung cancer. Thus, we aimed to investigate whether the COVID-19 pandemic had any influence on the clinical characteristics and diagnosis of patients with lung cancer. We collected clinical and demographic data of patients who were newly diagnosed with lung cancer at our hospital between February 2019 and July 2020. Overall, 387 patients with lung cancer were divided into the two groups for analysis: epidemic group (from February to July 2020) and pre-epidemic group (from February to July 2019). The source of diagnosis and clinical characteristics of the two groups were analysed. T-test and Mann-Whitney U were used for continuous variables, and Chi-squared or Fisher's exact test for categorical variable. We found that during the epidemic period, 110 cases of lung cancer were incidentally diagnosed during COVID-19 screening, accounting for 47.6% of all newly diagnosed lung cancer cases at our hospital. The proportions of patients who were diagnosed based on symptoms and physical examination in the epidemic group were 34.2% and 18.2%, respectively, while that in the pre-epidemic group were 41.7% and 58.3%, respectively. There was significant difference in the source of diagnosis between the two groups. In a subgroup analysis of the epidemic group, the average tumour volume of the patients diagnosed with COVID-19 screening was significantly smaller than that of the patients diagnosed with symptoms and physical examination. In conclusion, the continuation of the COVID-19 pandemic may impact the screening and clinical characteristics of lung cancer and require large-scale and longer-term observation.